Echinochloa crus-galli genome analysis provides insight into its adaptation and invasiveness as a weed - Longbiao Guo (Nature Portfolio, 2017)
Barnyardgrass is a problematic agricultural weed. Here, via genomic analysis, Guo et al. identify genes potentially underlying its success, including a gene cluster activated in response to co-cultivation with rice that leads to synthesis of the allelochemical DIMBOA.